Press Forward: Advancing Vaccine Production With High Hydrostatic Pressure Inactivation for Global Health Equity - Miss Martina Brandolini; Dr Alessandra Mistral De Pascali; Mr Giorgio Dirani; Mr Massimiliano Guerra; Ms Silvia Zannoli; Prof Pietro Rocculi; Dr Michele Morbarigazzi; Dr Davide Lelli; Dr Antonio Lavazza; Dr Francesca Battioni; Prof Monica Cricca; Prof Alessandra Scagliarini; et al. (International Journal of Infectious Diseases)
Introduction: Viral inactivation constitutes the basis of many immunoprophylaxis strategies, alongside subunit and, more recently, nucleic-acid-based vaccines. The growing and continuous demand for vaccine doses has stimulated research in the field, boosting the development of new viral inactivation techniques, like high hydrostatic pressure inactivation (HHP), already used in the food industry for controlling microbial contaminations. Studying the efficacy of this method to inactivate viruses may offer new possibilities. Methods: HHP-mediated inactivation of SARS-CoV-2 B.1 and BQ.1.1 lineages ultracentrifugation-purified viral isolates was carried out with a high-pressure system (Avure Technologies Inc.). Three different pressures, maintained for 5 minutes, were tested: 400, 500 and 600 MPa. Virus infectivity reduction was assessed on Vero E6 cell culture. The impact of the inactivation process on virion ultrastructure and on viral proteins’ antigenicity was evaluated by negative staining Transmission Electron Microscopy (TEM) and western blot. Immunogenicity was measured in a murine model (CD1 IGS mice) to assess its capacity to induce B- and T-cell-mediated responses at different time points after immunisation (ELISA, seroneutralisation and T-SPOT assays). Results: Inactivation assessment on Vero E6 cell culture highlighted that both variants were completely inactivated at 500 and 600 MPa, while virus isolates treated at 400 MPa retained infectivity, although replicating with slower kinetics. Even at the highest tested pressure, the viral particles were morphologically identifiable. Inactivation from 500 MPa nonetheless resulted in alterations of the outer surface, appearing smoother due to spikes damage. In agreement with evidence from TEM examination, while the ability of the spikes to bind antibodies was reduced compared with the non-HHP-inactivated control, other structural proteins, i.e., nucleocapsid and membrane, were not damaged. Inactivated viruses were thus capable to induce both an antibody and cell-mediated response in the murine model. Discussion: Preliminary results show HHP efficacy in producing viral inactivates that can efficiently be used as immunogens in murine animal models. The process has so far been validated against SARS-CoV-2, but can universally be used for other emerging and re-emerging viruses with a high impact on human and animal health. The same inactivation process is currently being evaluated for the inactivation of other viruses with high health impact, with promising pilot data. Conclusion: The development of a HHP viral inactivation method allowing the cost-effective production of large quantities of inactivated viral suspension (∼ 5€/litre) might represent an important turning point with a high intrinsic potential of clinical translation in the immunoprophylactic field for the development of new low-cost thermostable vaccines. In fact, not requiring a cold chain for distribution, they are suitable for use also in LMICs (Low- and Middle-Income Countries), which have historically been plagued by substantial disparities when it comes to public health policies, bridging the gap of vaccine access, distribution, and uptake.